Business location: strategic factor for the development of regions? One approach on industrial location policy of Bahia - Noelio Spinola; Carolina Spinola; Aliger Pereira (European Regional Science Association (ERSA), 2015)
In this paper we present a critical analysis of industrial location policy of the state of Bahia, in the period covered in between 1960s and 2000s, from the perspective of spatial economy. The paper reviews the formulation of the theory of location, through the contributions of its principal authors, evidencing the changes occurring in its epistemological basis with the advent of new transports and communication technologies. Through documentary research were analyzed localization strategy of industrial districts of Ilheus, Jequié, Vitória da Conquista and Juazeiro, the industrial centers of Subaé (in Feira de Santana) and Aratu and Camaçari Petrochemical Complex - largest integrated industrial complex in the southern hemisphere. The analysis concludes that the State of Bahia experience was not successful and that it was not related to the conditions formulated by the spatial economy. Despite what this theory advocates, industries attracted to Bahia did not have their effects extrapolated to other sectors of the regional economy, being in practice, enclaves. Some possible reasons for this fact are related to structural context of Brazilian economic and political system: the concentrating income model, which requires industrial companies to operate with a high coefficient of location, ie a tendency to spatial concentration; the industrial park is dedicated mainly to the production of intermediate goods, requiring to its viability the existence of economies of scale, agglomeration and urbanization, from which are only partly relieved the agribusiness and mineral processing companies; the lack of a strategy and industrial development policy was determinant in order for this space being subject to strong political will significantly marked by the authoritarism, which eliminated the integration of intersectoral actions, as well as an effective participation in the process from various segments of society, especially the business sector. From the spatial point of view, it appears that the macro locational definition of Bahias industrial districts was guided mainly by politics and secondarily relied much more on the analysis of urban hierarchy than the occurrence of effective economic possibilities and industrialization. Therefore, it follows the conclusion, answering the question that heads this article, as the facts indicate, that in order for the locational theories taking place in strategic regional development factors, it should be taken into account a number of other conditions, such as the local culture, the effective political system and market structure.
Keywords: R11; R12; 330; Spatial economics; Business location; Service economy; Regional development; Bah